The effects of early childhood dancesport intervention on executive function in preschool children: a randomized controlled trial - Wanxu Liu; Zilin Wang; Yixuan Liu; Xiaofen Li (Scientific Reports)
Abstract This study examines the effects of early childhood DanceSport intervention on executive functions (EFs) in preschoolers. A total of 214 children (96 aged 4–5, 118 aged 5–6) were randomly assigned to an experimental or control group. The experimental group participated in an 8-week early childhood DanceSport program (twice weekly, 45 min), while the control group engaged in regular activities. EFs—cognitive flexibility (CF), inhibitory control (IC), and working memory (WM), were assessed pre- and post-intervention using standardized measures: Dimensional Change Card Sort (DCCS) for CF, Attention Network Test for Children (ANT-C) for IC, and Backward Digit Span Test (BDST) for WM. The results revealed a significant time × group interaction effect in the DCCS, ANT-C, and BDST assessments (p < 0.01). A significant time × age interaction effect for reaction time (RT) was observed in the DCCS task (p = 0.001), while the ANT-C task showed a significant age × group interaction effect for RT (p = 0.003). Early childhood DanceSport may enhance EFs, with more pronounced improvements in CF for 5–6-year-olds and in IC for 4–5-year-olds. These findings support the integration of DanceSport into early education as a means to promote cognitive development and inform age-appropriate strategies for EF enhancement.